Adenoid Cystic Carcinoma Nasal - Sudarmanto, Yohanes; Soehartono; Angelina, Aina; Yudhanto, Hendy; Putri, Anggie (Jurnal Klinik dan Riset Kesehatan, 2022)
Background: Sinonasal neoplasms are uncommon. Adenoid cystic carcinoma (ACC) is the 2nd commonest sinonasal malignancy, characterized by an indolent and slow growth but relatively high local recurrence and distant metastasis rate. Surgical management followed by adjuvant radiation therapy is the mainstay of treatment for sinonasal ACC. Surgical approach is modified according to the tumor size and location.In general, prognosis of sinonasal neoplasms is poor. Factors that contribute the overall prognosis such as type of histopathological findings, absent of perineural or perivascular invasion and distant metastases, site of tumour, age of patient and treatment modality. Aim: To report a case of nasal ACC with regional metastases treated with surgical management followed radiation therapy. Case Report: A 70-years-old man came to the ENT clinic at RSUD dr. Saiful Anwar Malang with right nasal obstruction and history of right epistaxis for 12 months. The patient underwent surgical using lateral rhinotomy approach with Moure’s incision, histopatological specimen revealed a cribiform type ACC. Conclusion: Surgical management and adjuvant radiation therapy is the gold standard for sinonasal ACC Longterm evaluation is a mandatory according to the high incidence of local recurrence and distant metastases of sinonasal ACC.